2022
DOI: 10.1007/s42729-022-00907-8
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Machinery and Glyoxalase System Regulation Confers Salt Stress Tolerance to Wheat (Triticum aestivum L.) Plants Treated with Melatonin and Salicylic Acid

Abstract: Plant growth regulators melatonin (MT) and salicylic acid (SA) have potent roles in plant salt tolerance. However, only a few reports have studied the influence of their combined treatment on plant salt tolerance. The current study, as a first investigation, was aimed to evaluate the effect of MT and SA combined treatment on the antioxidant and glyoxalase defense machineries of salt-stressed wheat plants. In the present study, the potential role of 70 μM MT and/or 75 mg l−1 SA on mitigating salt injury (6.0 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 68 publications
8
24
0
Order By: Relevance
“…Salt stress can also induce oxidative stress by MG overproduction (Kamran et al 2020;Talaat and Todorova 2022). Consistent with this report, our study indicated a significant increase in barley MG content under 6.0 and 12.0 dS m −1 salinity levels.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Salt stress can also induce oxidative stress by MG overproduction (Kamran et al 2020;Talaat and Todorova 2022). Consistent with this report, our study indicated a significant increase in barley MG content under 6.0 and 12.0 dS m −1 salinity levels.…”
Section: Discussionsupporting
confidence: 91%
“…Various antioxidative strategies have been developed in plants to cope with the oxidative stress induced by salinity. Previous studies suggested that plant salt tolerance was normally associated with plant antioxidative capacity, namely ROS-scavenging or-detoxification ability (Talaat 2019b;Talaat and Todorova 2022). Our results revealed that when barley plants facing the oxidative injury caused by salt stress, change in the antioxidant enzymes activity was detected.…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…Plant hormones are critical for plant growth and development because they orchestrate intrinsic developmental programs as well as relay environmental stimuli [15][16][17]. Among them, brassinosteroids (BRs), a group of steroidal phytohormones, regulate a variety of plant physiological processes such as cell division, cell elongation, seed germination, stomata development, vascular differentiation, plant architecture, flowering, senescence, and abiotic stress responses [18][19][20].…”
Section: Introductionmentioning
confidence: 99%